2018
DOI: 10.1111/cch.12563
|View full text |Cite
|
Sign up to set email alerts
|

The Uganda version of the Pediatric Evaluation of Disability Inventory (PEDI). Part I: Cross‐cultural adaptation

Abstract: Background: The Pediatric Evaluation of Disability Inventory (PEDI) was developed and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…The psychometric analyses in the present study support the validity of the culturally adapted PEDI‐UG (Kakooza‐Mwesige et al, ). The analyses demonstrated that the PEDI‐UG fulfilled most of the recommended criteria for validity after some adjustments and that it showed excellent test–retest reliability.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The psychometric analyses in the present study support the validity of the culturally adapted PEDI‐UG (Kakooza‐Mwesige et al, ). The analyses demonstrated that the PEDI‐UG fulfilled most of the recommended criteria for validity after some adjustments and that it showed excellent test–retest reliability.…”
Section: Discussionsupporting
confidence: 82%
“…Some uncertainty still remains in the Mobility domain, in which less than 60% of the variance was explained by measures and more than 5% of items were misfit. At this stage, we have chosen to keep some of these items for further analyses in a clinical population because they may be clinically important, see Kakooza‐Mwesige et al (). In addition, there was a positive point‐biserial correlation for all the items and a low effect of other dimensions (less than 5% of variance was explained by a second dimension), which indicates satisfactory unidimensionality (Haley et al, ; Linacre, ; Schumacker, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations